Amb a 1 isoforms: Unequal siblings with distinct immunological features. Issue 12 (14th June 2017) - Wolf, M.; Twaroch, T. E.; Huber, S.; Reithofer, M.; Steiner, M.; Aglas, L.; Hauser, M.; Aloisi, I.; Asam, C.; Hofer, H.; Parigiani, M. A.; Ebner, C.; et al.
Abstract: Background: Ragweed pollen represents a major allergy risk factor. Ragweed extracts contain five different isoforms of the major allergen Amb a 1. However, the immunological characteristics of Amb a 1 isoforms are not fully investigated. Here, we compared the physicochemical and immunological properties of three most important Amb a 1 isoforms. Methods: After purification, the isoforms were physicochemically characterized, tested for antibody binding and induction of human T‐cell proliferative responses. Their immunological properties were further evaluated in vitro and in vivo in a mouse model. Results: Amb a 1 isoforms exhibited distinct patterns of IgE binding and immunogenicity. Compared to Amb a 1.02 or 03 isoforms, Amb a 1.01 showed higher IgE‐binding activity. Isoforms 01 and 03 were the most potent stimulators of patients' T cells. In a mouse model of immunization, Amb a 1.01 induced higher levels of IgG and IgE antibodies when compared to isoforms 02 and 03. Interestingly, ragweed‐sensitized patients also displayed an IgG response to Amb a 1 isoforms. However, unlike therapy‐induced antibodies, sensitization‐induced IgG did not show IgE‐blocking activity. Conclusion: The present study showed that naturally occurring isoforms of Amb a 1 possess different immunogenic and sensitizing properties. These findings should be considered when selecting sequences for molecule‐based diagnosis and therapy for ragweed allergy. Due to its high IgE‐binding activity, isoform Amb a 1.01 should be included in diagnostic tests. In contrast, due to their limited B‐ and T‐cell cross‐reactivity patterns, a combination of different isoforms might be a more attractive strategy for ragweed immunotherapy.